NILAI-NILAI CIVIC CULTURE PADA PERKAWINAN SUKU BANJAR DI DESA LAHANG BARU KECAMATAN GAUNG KABUPATEN INDRAGIRI HILIR - Hendra.s, Hendra.s; Zahirman, Zahirman; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was motivated by the shifting of civic culture values inthe Banjar tribe marriage in Desa Lahang Baru, Kecamatan Gaung, KabupatenIndragiri Hilir. The formulation of the problem in this study is: "Are there civic culturevalues in the Banjar tribe marriage in Desa Lahang Baru, Kecamatan Gaung,Kabupaten Indragiri Hilir ". This study was a qualitative study carried out in DesaLahang Baru, Kecamatan Gaung, Kabupaten Indragiri Hilir during the time periodfrom March 2019 to September 2019. The informants in this study were the Head ofLahang Baru, saleh, traditional leaders in Lahang Baru, and the community. Datacollection techniques in this study used primary data in the form of observations andinterviews and secondary data in the form of literature and documentation studies. Thedata analysis technique used is descriptive qualitative. The results of the study: Civicculture values in the aspect of civilization have shown a shift. The civic culture values ofthe Banjar tribe in the aspect of responsibility have also shifted. Civic culture values inthe Banjar tribal marriage on the aspect of self-discipline are rarely done. Civic culturevalues in the Banjar tribe marriage on the aspect of concern have been seen to decline.Civic culture values in the aspect of tolerance are no longer felt by the Banjar tribecommunity. Civic culture values in the aspect of loving the motherland can beconcluded that the informant feels proud to be a community of customary lawcommunities of the Banjar tribe, the informant will try to maintain the existence oftraditions that have been inherited from ancestors.Key Words: Values, Civic Culture